2017
DOI: 10.1596/1813-9450-8140
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Presource Curse? Oil Discoveries, Elevated Expectations, and Growth Disappointments

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 21 publications
3
27
0
Order By: Relevance
“…This provides suggestive evidence that the quality of institutions may be important in shaping citizen expectations on the impact of oil discoveries. This finding concurs with earlier findings of Cust and Mihalyi (2017a) who showed that countries with weaker political institutions experience lower growth after a discovery relative to the period before a discovery and compared to contemporaneous growth forecasts by the IMF.…”
Section: Ja Kufoursupporting
confidence: 92%
See 2 more Smart Citations
“…This provides suggestive evidence that the quality of institutions may be important in shaping citizen expectations on the impact of oil discoveries. This finding concurs with earlier findings of Cust and Mihalyi (2017a) who showed that countries with weaker political institutions experience lower growth after a discovery relative to the period before a discovery and compared to contemporaneous growth forecasts by the IMF.…”
Section: Ja Kufoursupporting
confidence: 92%
“…1 This exuberance stems from the expectation that windfalls from resource extraction might bring a significant shift in the economic trajectory of their economies. Recent research however suggests that in some countries expectations can overshoot the benefits subsequently felt, coinciding with growth disappointments, a phenomenon known as the "presource curse" (Cust and Mihalyi, 2017a). Various authors propose mechanisms whereby overly optimistic expectations about future rents, triggered by announcements of major resource discoveries, may induce governments to embark on unplanned spending including through excessive borrowing (Mansoorian, 1991;Arezki et al, 2017;Collier, 2017).…”
Section: Ja Kufourmentioning
confidence: 99%
See 1 more Smart Citation
“…They have not yet converted hydrocarbon rents into other sources of export revenues needed to grow and diversify. They also often face major challenges attracting commercial investors and raising affordable finance, although some of them, for example, Mozambique and Ghana, have heavily borrowed against expected extractive revenues and are already burdened with the high cost of debt service (Cust, J. and D. Mihalyi, 2017). Climate policy leaders could help these countries adjust to an LCT through technology, financial cooperation, and trade agreements that would provide them with revenue visibility to invest in low-carbon growth and diversification.…”
Section: What Are the Impacts Of Climate Change On The Public Sector?mentioning
confidence: 99%
“…The alternative scenario increases the prospect of plunder and mismanagement. Indeed, recent empirical work has argued that critical thresholds exist in polices and institutions that determine whether resource abundance leads to perverse political choices (Casselli and Tesei 2016) and whether major oil discoveries lead to short-run growth disappointments or not (Cust and Mihalyi 2017).…”
mentioning
confidence: 99%